UPAYA PENINGKATAN MINAT DAN PRESTASI BELAJAR SISWA SMKN 3 KOTA JAMBI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION - SUHUDI SUHUDI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
This study aims to increase the interest and learning achievement of Class XII TIPTL 2 SMK Negeri 3 Jambi City students in the 2018/2019 academic year by using the Group Investigation Type Cooperative Learning Model in the subject of Electrical Motor Installation (IML). This research method is CAR (Classroom Action Research). The research population used all XII grade students of SMK Negeri 3 Jambi City and the subject of this research was the XII grade TIPTL 2 students consisting of 23 students. The research was carried out in two cycles, assisted by two observers, collecting data using tests and observations. The results show improvement using this model. This is indicated by an increase in the percentage of the average results of the questionnaire sheet interest in learning Electrical Power Utilization Installation Engineering (TIPTL) each cycle, namely in the pre-cycle student interest by 61.12% increased to 66,729% in the first cycle, and increased in the second cycle. to be 80.145%. In addition, the average value of student learning achievement in Electrical Motor Installation (IML) has increased, namely in the pre-cycle completeness of 55.313 with a percentage of 31.25% (8 students), in the first cycle it increased to 70.21 with a percentage of completeness 59.38 % (14 students), while in the second cycle it increased to 80.51 with a completeness percentage of 81.25% (19 students). Based on the research results, it is expected that teachers can use the Group Investigation Type Cooperative Learning Model which is one of the learning models that can increase students' interest and learning outcomes for Electric Motor Installation (IML). ABSTRAKPenelitian ini bertujuan untuk meningkatkan minat dan prestasi belajar siswa Kelas XII TIPTL 2 SMK Negeri 3 Kota Jambi tahun pelajaran 2018/2019 dengan menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation pada mata pelajaran Instalasi Motor Listri (IML). Metode penelitian ini adalah PTK (Penelitian Tindakan Kelas). Populasi penelitian menggunakan seluruh siswa kelas XII SMK Negeri 3 Kota Jambi dan subjek penelitian ini yaitu siswa kelas XII TIPTL 2 terdiri dari 23 siswa. Penelitian dilaksanakan dua siklus, dibantu oleh dua observer, pengumpulan data menggunakan tes dan pengamatan. Hasilnya menunjukkan peningkatan dengan menggunakan model ini. Hal ini ditunjukkan dengan adanya peningkatan persentase hasil rata-rata lembar angket minat belajar Teknik Instalasi Pemanfaatan Tenaga Listrik (TIPTL) setiap siklusnya, yaitu pada pra siklus minat siswa sebesar 61,12% meningkat menjadi 66,729% pada siklus I, dan meningkat pada siklus II menjadi 80,145%. Selain itu, nilai rata-rata prestasi belajar Instalasi Motor Listri (IML) siswa mengalami peningkatan yaitu pada pra siklus ketuntasan sebesar 55.313 dengan persentase 31,25% (8 siswa), pada siklus I meningkat menjadi 70,21 dengan persentase ketuntasan 59,38% (14 siswa), sedangkan pada siklus II meningkat menjadi 80,51 dengan persentase ketuntasan 81,25% (19 siswa). Berdasarkan hasil penelitian diharapkan kepada para guru agar dapat menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation yang merupakan salah satu model pembelajaran yang mampu meningkatkan minat dan hasil belajar Instalasi Motor Listri (IML) siswa.